2011
DOI: 10.5433/1679-0359.2011v32n4p1513
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa de antígenos e anticorpos contra Circovírus Suíno II em suínos com e sem sintomatologia da síndrome multisistêmica do definhamento em granjas comerciais mineiras

Abstract: Circovirus Suíno Tipo-2 (CSV-2) é um vírus não-envelopado, DNA fita única circular, classificado na família de Circoviridae, relacionado à Síndrome Multisistêmica do Definhamento de Suínos (SMDS) de leitões. A técnica de Imuno-Histoquímica (IHQ) é aplicada na detecção de antígenos do (CSV-2) em tecido lesionados. Entretanto, suínos infectados com CSV-2 assintomáticos ou com infecções subclínicas podem disseminar o vírus no plantel. A pesquisa de anticorpos contra o CVS-2 em porcos aparentemente saudáveis pode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thus, seroreactive animals may be acting as possible sources of viral infection until the final stage of the production cycle, regardless of the clinical development of the disease. The virus can be spread within the herd due to the presence of asymptomatic animals and subclinical infections (Barbosa et al, 2011;Rose et al, 2012). Mesu et al (2000) reported that PCV2 infections occur systematically in pigs, and other factors, such as management, housing, and/or concomitant bacterial and viral infections, are probably necessary to induce the onset of the syndrome in the herd.…”
Section: In Commercial Farmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, seroreactive animals may be acting as possible sources of viral infection until the final stage of the production cycle, regardless of the clinical development of the disease. The virus can be spread within the herd due to the presence of asymptomatic animals and subclinical infections (Barbosa et al, 2011;Rose et al, 2012). Mesu et al (2000) reported that PCV2 infections occur systematically in pigs, and other factors, such as management, housing, and/or concomitant bacterial and viral infections, are probably necessary to induce the onset of the syndrome in the herd.…”
Section: In Commercial Farmsmentioning
confidence: 99%
“…Serological surveys conducted from 1989 to 2011 on the European, Asian, and American continents have shown PCV2 seroreactivity ranging from 25 to 98% in finishing pigs (Mesu et al, 2000;Rodriguez-Arrioja et al, 2000;Zhou et al, 2006;Barbosa, Martins, Esteves, & Freitas, 2011). A total of 470 (81.74%) out of the 575 evaluated sera were reactive, being 190 (40.43%) low, 265 (56.38%) medium, and 15 (3.19%) high.…”
mentioning
confidence: 99%
See 1 more Smart Citation